2015
DOI: 10.1155/2015/724715
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting Key Genes Regulated by miRNAs in Dysfunctional Crosstalk Pathway of Myasthenia Gravis

Abstract: Myasthenia gravis (MG) is a neuromuscular autoimmune disorder resulting from autoantibodies attacking components of the neuromuscular junction. Recent studies have implicated the aberrant expression of microRNAs (miRNAs) in the pathogenesis of MG; however, the underlying mechanisms remain largely unknown. This study aimed to identify key genes regulated by miRNAs in MG. Six dysregulated pathways were identified through differentially expressed miRNAs and mRNAs in MG, and significant crosstalk was detected betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Moreover, exosomal miR‐106a‐5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep‐sequencing in the present study, miR‐106a‐5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, and esophageal squamous‐cell carcinoma . Similarly, miR‐106a‐5p dysregulation has been reported in T‐cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Moreover, exosomal miR‐106a‐5p expression was shown to be negatively correlated with patient QMGS, indicating its association with MG clinical typing and severity. Interestingly, one of the dysregulated miRNAs by deep‐sequencing in the present study, miR‐106a‐5p has been previously shown to be associated with the pathogenesis of many cancers, including melanoma, colorectal and gastric cancer, MG, and esophageal squamous‐cell carcinoma . Similarly, miR‐106a‐5p dysregulation has been reported in T‐cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets .…”
Section: Discussionsupporting
confidence: 59%
“…[27][28][29][30] Similarly, miR-106a-5p dysregulation has been reported in T-cells of patients with immune diseases, and may inhibit the proliferation, migration, and invasion of carcinoma cells by modulating various mRNA targets. 24,31 Notably, CD4+ T and Th17 cells are known to mediate thymic changes that are associated with MG pathogenesis, 32 and it has been suggested that miR-106a-5p may suppress the differentiation of Th17 cells and downregulate the production of CD4+ T cells during the relapse phase of multiple sclerosis and in MG. 24,25 The above reasons explain why miR-106a-5p was chosen for further verification by RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…A P value < 0.05 was considered to have a significant difference. MicroRNA target genes were predicted using the following miRNA target prediction tools: miRanda (August 2010 release) [31] and TargetScan (http://www.targetscan.org/ vert_71/) [32]. Only genes predicted by both databases were chosen as conjectural miRNA targets for pathway analysis.…”
Section: Mirna Profiling By Exiqon Mirna Qpcr Panelmentioning
confidence: 99%
“…To our knowledge, there are few studies that examine the role of miRNAs for cross-talked pathway able to correctly discriminate normal versus BC samples. Recently, in myasthenia gravis Cao et al [ 26 ] calculated the cross-talk between pathways, identified by pathway-enriched analysis based on a cumulative hypergeometric distribution. They obtained key genes regulated by miRNAs, and these miRNAs were found to mediate cross-talk.…”
Section: Introductionmentioning
confidence: 99%